BUSINESS DIFFERENTIATION STRATEGY OF ANTIMICROBIAL PRODUCTS IN THE COVID-19 PANDEMIC - Rachmiarti Kusumah, Judiatin (Dinasti Publisher, 2020)
The Covid-19 pandemic that has struck the world worldwide has had a major impact, particularly on the economic and socio-cultural conditions of every person in every country. No exception in Indonesia, which has not escaped and is also affected by the global pandemic. There is a slowdown in the growth process in the economic and financial sectors. This is the result of efforts to stop the spread of the virus with a lock-down action country in the world, and the implementation of the WFH (Work From Home) program and the PSBB (Large-Scale National Limitation) in Indonesia is having an effect for most industrial companies to slow down the business. This situation has a major impact on conditions in almost all companies where business is slowing down. There has also been a decline in activity in manufacturing companies producing paints, as consumer demand for paint products has been drastic due to the many delays in the process of building and building, and the process of painting houses and buildings has been stopped by painters. PT XYZ Raya, a national paint company that realizes competitive advantages between paint manufacturers, develops a differentiation strategy for paint products that meets the conditions and needs of paint consumers under the current pandemic conditions, namely antimicrobial paint products that can prevent this and inhibit the growth of viruses, germs and bacteria on the walls of our houses. So that family health can be maintained by using these antimicrobial wall paint products. The product differentiation strategy, in this case wall paint, is an embodiment of one of the company's competitive strategies according to Michael Porter's generic strategy